The Impact of Digital Screens on Eye and Nervous System Health - Gajewski, Witold; Górski, Jan; Janecka, Julia; Hofman, Michał; Skoczek, Weronika; Gałęcki, Wiktor (Journal of Medical Science, 2025)
Introduction. The increasing reliance on digital technology has led to a significant rise in daily screen exposure, raising concerns about its potential impact on eye health and the nervous system. Prolonged screen use is associated with conditions such as dry eye disease (DED), computer vision syndrome (CVS), progressive myopia, sleep disturbances, mental fatigue, and screen addiction - especially among children and adolescents.Material and methods. A narrative review of peer-reviewed articles, systematic reviews, and meta-analyses indexed in PubMed and Google Scholar was conducted. Boolean search strategies combined terms related to digital screens, ocular health, neurocognitive effects, and preventive interventions. Studies published up to 2025, with emphasis on data from 2020-2025, were included. The review focused on both ophthalmological and neurological consequences of screen exposure.Results. Current evidence indicates a strong correlation between prolonged screen use and the incidence of DED, CVS, and myopia. Neurocognitive impacts include circadian rhythm disruption due to blue light exposure, sensory overload, mental fatigue, and early signs of attentional deficits – especially in younger populations. Screen addiction amplifies these risks. Although some mitigation strategies, such as the 20-20-20 rule and digital detox programmes, have demonstrated effectiveness, others, like blue light filters, show inconsistent results.Conclusions. Prolonged use of digital screens has been shown to affect both visual and neurological health adversely. While complete avoidance is unrealistic, adopting healthy screen habits and evidence-based preventive strategies is critical. Further longitudinal research is essential to clarify long-term effects and support informed public health recommendations.
Keywords: eye health; mental health; screen addiction; preventive strategies; screen time management